Behavioral And Biochemical Approaches On The Therapeutic Effectiveness Of Leucas Aspera In Managing Trichloroethylene-Induced Neurotoxicity (The Review of Diabetic Studies, 2025)
The widely used chlorinated solvent, trichloroethylene (TCE), has been closely linked to neurotoxicity and the emergence of pathologies resembling Parkinson's disease (PD). This is mostly because TCE can cause neuronal damage, oxidative stress, and mitochondrial dysfunction. TCE exposure is a crucial experimental paradigm for researching neurodegeneration because these changes not only upset the metabolic balance but also affect behavioral function in individuals, causing major imbalance and instability. Plant-based neuroprotective drugs have gained attention recently as safer substitutes for treating brain damage brought on by toxins. In this study, the potential of the Methanolic extract of Leucas aspera, a medicinal plant renowned for its antioxidant and neuroprotective properties, to mitigate TCE-induced neurotoxicity in Wistar rats was investigated. Both behavioral and biochemical parameters are beneficial in examining oxidative stress and evaluating the effectiveness of the treatment in managing PD. The Rotarod test for motor coordination, the tail suspension test for depressive-like behavior, and the raised plus maze for anxiety-related reactions were among the behavioral evaluations. Superoxide dismutase (SOD) and catalase (CAT) activity were evaluated as indicators of antioxidant defense, while lipid peroxidation (LPO) was examined as an indicator of oxidative damage in the hippocampus. The results showed that rats exposed to TCE exhibited increased anxiety-like behavior, extended immobility, and marked deterioration in motor coordination and enzyme estimation using Acetylcholinesterase (AChE). Elevated lipid peroxidation levels and a significant decrease in SOD and CAT activity coincided with these behavioral changes, indicating that oxidative stress had been induced in the hippocampus tissue. Through the restoration of motor function, the reduction of depressive-like characteristics, and the normalization of anxiety indicators, treatment with Leucas aspera extract markedly improved behavioral results. Leucas aspera extract also decreased oxidative damage by increasing SOD and CAT activity toward normal levels and decreasing lipid peroxidation. When combined, these findings suggest that Leucas aspera has high neuroprotective potential against TCE-induced neurotoxicity, most likely via its antioxidant mechanism, and could be a viable natural treatment option for Parkinson's disease.